Prescribing and Self-Regulating Heated Water-Based Exercise by Rating of Perceived Exertion in Older Individuals With Hypertension - Marçal, Isabela Roque [UNESP]; Fernandes, Bianca [UNESP]; do Amaral, Vanessa Teixeira [UNESP]; Pelaquim, Renato Lopes; Ciolac, Emmanuel Gomes [UNESP] (Human Kinetics, 2022)
We aimed to analyze the usefulness of the 6-20 rating of perceived exertion (RPE) scale for prescribing and self-regulating high-intensity interval (HIIE) and moderate-intensity continuous (MICE) aerobic exercise performed in a heated swimming pool (32 °C). Fifteen older individuals (65 ± 3 years) treated for hypertension underwent a symptom-limited maximal graded exercise test to determine their heart rate at anaerobic threshold, and respiratory compensation point. On different days, participants were randomized to HIIE (walking/jogging between 11 and 17 of RPE; 25 min) and MICE (walking at 11-13 of RPE; 30 min). Heart rate during the low-intensity intervals of HIIE and MICE remained below the graded exercise test's heart rate at anaerobic threshold (−7 ± 18 bpm/−16 ± 15 bpm) and respiratory compensation point (−18 ± 18 bpm/−30 ± 16 bpm), respectively, and maintained in the aerobic training zone during the high-intensity intervals of HIIE (+8 ± 18 bpm/−4 ± 19 bpm). The RPE scale at 15-17 is a useful tool for prescribing and self-regulating heated water-based HIIE and may have important implications for water-based exercise in older individuals with hypertension.
Keywords: Aquatic exercise; blood pressure; Borg's scale; older adults